2010
DOI: 10.3109/10428194.2010.487958
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplant following chemotherapy containingl-asparaginase as a promising treatment for patients with relapsed or refractory extranodal natural killer/T cell lymphoma, nasal type

Abstract: The prognosis of advanced extranodal NK/T cell lymphoma (ENKTL) is poor. Allogeneic hematopoietic stem cell transplant (allo-HSCT) has been suggested to be a promising treatment for this disease, but its utility has yet to be established. Here we retrospectively analyzed five cases of ENKTL treated with allo-HSCT in our institute. After induction chemotherapy, disease status at allo-HSCT was second CR in three patients and refractory in two patients. All patients received a myeloablative conditioning regimen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Two studies were conducted before L-asparaginse-containing regimens were used, 11,14 whereas two studies contained some patients treated with L-asparaginase-containing regimens. 12,13 Owing to the heterogeneity and small numbers of patients involved, most studies only stressed the feasibility of allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were conducted before L-asparaginse-containing regimens were used, 11,14 whereas two studies contained some patients treated with L-asparaginase-containing regimens. 12,13 Owing to the heterogeneity and small numbers of patients involved, most studies only stressed the feasibility of allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…6,10 Owing to a putative graft-versus-lymphoma effect, allogeneic HSCT has also been explored, especially in poor-risk patients with advanced-stage disease. [11][12][13] In an earlier study of allogeneic HSCT in 28 patients with CD56-positive neoplasms, which included 22 patients with NK/T-cell lymphoma, the 2-year OS and PFS were 40% and 34%, with a TRM of 20-30% depending on the conditioning regimen. 11 Unfortunately, results of patients with NK/T-cell lymphomas were not separately described, and the survivals were not spectacular in comparison with L-asparaginasecontaining regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective analyses have shown that some patients who underwent HSCT obtained a long-term CR [58,59], suggesting HSCT may be a cure-oriented therapy for disseminated ENKL, although these data were obtained before 'the SMILE era'. Recently, there have been accumulating data on the promising efficacy of allogeneic HSCT for relapsed or refractory ENKL [60,61], and experts in East Asia recommend allogeneic HSCT for this population [49,62].…”
Section: Comments On Hsct For Disseminated Enklmentioning
confidence: 99%
“…В 2015 г. были опубликованы данные корейского проспективного исследования, где продемонстрированы более высокие показатели ОВ и БПВ больных, получивших после индукционной SMILE-терапии высокодозную консо-лидацию с последующей аутотрансплантацией гемо-поэтических клеток [46]. По данным зарубежных ис-точников литературы, трансплантация аллогенного костного мозга (аллоТКМ) не является до конца из-ученным методом лечения ЭНКТЛ и применяется в основном для консолидации ремиссии при рецидив-ных и рефрактерных формах заболевания [47]. Тем не менее у части больных с неблагоприятным прогнозом заболевания удается достичь длительной полной ре-миссии после выполнения аллоТКМ [48].…”
Section: Introductionunclassified